Thermal decomposition of ionic solids - Galwey, Andrew K. (Andrew Knox) (Studies in physical and theoretical chemistry, 1999)
The principal objective of this book is to stimulate interest in research that will extend available theory towards a greater understanding of the steps involved in solid-state decompositions and the properties of solids that control reactivities. Much of the activity in this field has been directed towards increasing the range of reactants for which decomposition kinetic data is available, rather than extending insights into the fundamental chemistry of the reactions being studied. The first part of the book (Chapters 1-6) is concerned with theoretical aspects of the subject. The second part (Chapters 7-17) surveys groups of reactions classified by similarities of chemical composition. The final Chapter (18) reviews the subject by unifying features identified as significant and proposes possible directions for future progress. Studies of thermal reactions of ionic compounds have contributed considerably to the theory of solid-state chemistry. Furthermore, many of these rate processes have substantial technological importance, for example, in the manufacture of cement, the exploitation of ores and in the stability testing of drugs, explosives and oxidizing agents. Despite the prolonged and continuing research effort concerned with these reactions, there is no recent overall review. This book is intended to contribute towards correcting this omission. The essential unity of the subject is recognized by the systematic treatment of reactions, carefully selected to be instructive and representative of the subject as a whole. The authors have contributed more than 200 original research articles to the literature, many during their 25 years of collaboration. Features of this book: & bull; Gives a comprehensive in-depth survey of a rarely-reviewed subject. & bull; Reviews methods used in studies of thermal decompositions of solids. & bull; Discusses patterns of subject development perceived from an extensive literature survey. This book is expected to be of greatest value and interest to scientists concerned with the chemical properties and reactions of solids, including chemists, physicists, pharmacists, material scientists, crystallographers, metallurgists and others. This wide coverage of the literature dealing with thermal reactions of solids will be of value to both academic and industrial researchers by reviewing the current status of the theory of the subject. It could also provide a useful starting point for the exploitation of crystalline materials in practical and industrial applications. The contents will also be relevant to a wide variety of researchers, including, for example, those concerned with the stabilities of polymers and composite materials, the processing of minerals, the shelf-lives of pharmaceuticals, etc.